Can geocaching be an indicator of cultural ecosystem services? The case of the montado savannah-like landscape (Ecological Indicators, 2019)
Cultural Ecosystem Services (CES) are difficult to assess and are seldom considered by land managers. Geocaching, an outdoor game that uses Global Positioning System (GPS) enabled devices to find hidden containers (geocaches) in certain locations, has been seldom used as a data source to assess CES. However, contrary to other crowdsourcing databases, geocaching allows to associate particular experiences to accurate locations. Furthermore, databases generated by geocachers provide an ideal case to compare revealed preferences (the frequency of visits to a specific geocache) with stated preferences (a posteriori evaluation of each location). We tested the relevance of geocaching databases as CES indicators using a dataset of 50 818 geocaches spread across continental Portugal, over eight land-use classes, with a focus on the montado (a high nature value farmland found in Southwestern Iberian Peninsula). We found that site visitation frequency was related with its availability, showing no revealed preference towards any land use. However, site evaluations by geocachers, measured either through the number of words describing the experience, the number of photos taken, or the number of votes for “favourite geocaches”, showed marked differences in their stated preferences, with higher appreciation for open land uses in general, and montado in particular, especially when compared to other forested landscapes. Our results may contribute to the design of regional development and land-use management policies of this threatened landscape, since they show the system’s strong potential as CES provider and, consequently, promoter of diversification of activities.